Exploring the Feasibility of Algae Building Technology in NSW. (2017) - Wilkinson, Sara; Stoller, Paul; Ralph, Peter; Hamdorf, Brenton; Catana, Laila Navarro; Kuzava, Gabriela Santana
Abstract: For some time, Biochemists have been exploring the potential to produce biofuels as an alternative to fossil fuel energy. Biofuels can be derived from crops such as corn, soybean and sugarcane however these crops can contribute to water scarcity and deforestation. Furthermore, large areas of land are used that could otherwise be used for food production. Another possibility is to use microalgae, which does not have the disadvantages associated with crop-based biofuels. Depending on conditions, microalgae can produce bio compounds that are converted into biofuels. The built environment is responsible for around 40 to 50% of total greenhouse gas emissions through fossil fuel consumption. Not only is it necessary to design and to retrofit our built environment to be more energy efficient, but it is also necessary to consider alternative fuel sources. To date, this has mostly focused on solar, wind and geothermal sources, however one residential building in Hamburg Germany has adopted algae building technology in the form of façade panels which act as a source of energy for heating the apartments and for hot water. The climate in northern Germany is very different to Australia, and the question arises; what is the feasibility to adopt algae building technology in New South Wales? There are issues around the physical and technical aspects of the technology, the social and environmental aspects, the regulatory and planning aspects, as well as the economic considerations. This paper reports on a study with key stakeholders in New South Wales to explore barriers and drivers associated with the adoption of algae building technology.